s-(-13)=46

Simple and best practice solution for s-(-13)=46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for s-(-13)=46 equation:


Simplifying
s + -1(-13) = 46

Multiply -1 * -13
s + 13 = 46

Reorder the terms:
13 + s = 46

Solving
13 + s = 46

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + s = 46 + -13

Combine like terms: 13 + -13 = 0
0 + s = 46 + -13
s = 46 + -13

Combine like terms: 46 + -13 = 33
s = 33

Simplifying
s = 33

See similar equations:

| 4=2+2t | | 4(2-x)+5=-3(2x+3)-12 | | n/7-6=14 | | -(b+a)= | | 16cos^4(x)= | | 10(8+x)=260 | | w/-9=5 | | 16(x^3+4x)=0 | | -16p=-64 | | 15(a-7)=-7-8 | | 52x=150 | | 7(x+2)-4m=2(m+10) | | 16cos^4(x)-12cos^2(x)=-1 | | Y+6(-3)=5 | | y-(-6)=53 | | 5x+2d-2x=1 | | 5sinx-4=0 | | u/-9=(-9) | | 2(L+12)=36 | | 3y+2=1-7y | | X-2.4=5.1 | | (p-4)(p+3)=0 | | 16cos^4(x)-12cos^2(x)+1=0 | | 68=t+(-14) | | Z-15=30 | | u-(-14)=19 | | 4*[1-(4-15)/3] | | 6i(4+2i)=equation | | (b-5)(2b-1)=0 | | 5(x+1)-x=4x+5 | | Y(9+y)=y*9+y*y | | -(2n+2n)= |

Equations solver categories